PENGGUNAAN METODE PSIKOLOGIS DALAM MENGATASI MASALAH UNTUK MENINGKATKAN PEMAHAMAN BAHASA INDONESIA SISWA SD - Tin Susanti; Evi Chamalah; Rida Fironika Kusumadewi (Jurnal Pendidikan Sultan Agung, 2025)
Psychological methods in Indonesian language lessons focus on approaches that consider the psychological aspects of students to enhance learning effectiveness. One commonly used method is constructivism, where students are encouraged to build their own understanding based on prior experiences and knowledge. The aim of this study is to explore and analyze the effectiveness of using psychological methods to improve elementary students' comprehension of the Indonesian language. By applying educational psychology techniques such as game-based learning, positive reinforcement, and individualized learning approaches, it is hoped that students can more easily grasp Indonesian language concepts. Data collection techniques through qualitative methods include direct classroom observation and interviews with teachers and students. Research on the use of psychological methods to address issues in improving elementary students' understanding of the Indonesian language shows significant results. The applied psychological methods help students overcome emotional and cognitive barriers that often disrupt their learning process. With this approach, students can be more focused and motivated in learning the Indonesian language. Moreover, these methods boost students' confidence in their language skills, as they feel more understood and emotionally supported. The results of this study emphasize the importance of psychological approaches in learning, which do not only focus on academic aspects.